Reformas legales al art. 142 del código orgánico integral penal relacionado a las circunstancias agravantes en los delitos de femicidio - Sarango Ajila, Angel Roberto (2014)
The Constitution of the Republic Ecuador in Art 66, paragraph 1 and 3 guarantees everyone the right to life and personal integrity, innate rights of the people, without which none of the other rights can be exercised. The Art. 75 of the Constitution also recognizes and guarantees the right to justice and the effective protection of all people, therefore the state as guarantor of the rights of the people, must protect these rights by issuing clear laws and harmonic, as determined pursuant to Art. COIP 13 prohibits the broad interpretation of the law in criminal matters. In our country, there is a high rate of deaths from violent acts against women, why, typified in the Integral Penal Code, the crime of femicide, this is the crime committed by men against women derived of relationship violence motivated by hatred, contempt, revenge, pleasure or a sense of ownership of women by their partners. Article 141 of the Penal Code Integral refers to the crime of femicide noting that the person who, as a result of power relations expressed in any violence, kills a woman by virtue of being or their gender, shall be punished with imprisonment of twenty-two to twenty-six years. COIP Article 142, establishes aggravating circumstances of the crime of femicide, if one or more of the following circumstances in which the maximum penalty provided for in the preceding article shall be imposed: Have intended to establish or reestablish a relationship or intimacy with the victim; Exists or has existed between the perpetrator and the victim family relationships, marital, cohabitation, intimacy, dating, friendship, companionship, work, school or any other involving trust, subordination or superiority; If the offense is committed in the presence of daughters, child or any other relative of the victim; and the victim's body is exposed or thrown in a public place. In my opinion I think it is necessary to reform the Art. 142 COIP establishing other aggravating circumstances in order that the judge may have clear guidelines and impose sentences and adequately ensuring the right to justice and effective protection of victims crime, such as: a). Penetrating the residence of the abused woman or where it inhabits, when the conjugal or marital relationship of women victims of violence with the defendant is in a situation of separation of fact or law, or when the marriage was dissolved by a judgment; b) Penetrate the residence of women victims of violence or where it dwells, using the bond of consanguinity or affinity .; c) Run it with weapons, items or instruments; d) Run it to the detriment of a pregnant woman; c) Run it in sheaf or group of persons; e) If the perpetrator of the crime is a public official in the exercise of their functions; f) perpetrate detriment of particularly vulnerable persons with physical or mental disabilities; and. g) Perform actions that deprive the victim of the ability to discern a result of using fraudulent means or exciting or narcotic substances. Also I think the legislature should leave open the possibility that considered as aggravating in the crime, either established in Article 47 of the Penal Code Integral, as they are applicable.